Case Report: A novel EPAS1 mutation in a case of paraganglioma complicated with polycythemia and atrial septal defect - Yang, Haiyan; Chen, Yue; Liu, Kai; Zhao, Liming (Frontiers in Endocrinology, 2023)
Background Paraganglioma is a rare neuroendocrine tumor and is highly associated with hereditary susceptibility genes, often occurring as part of a genetic syndrome. The genetic heterogeneity of paraganglioma poses challenges in diagnosis, counseling, and clinical management. Case summary We present the case of a 60-year-old woman with hypertension, atrial septal defect, and polycythemia, who experienced paroxysmal palpitations, sweating, headache, abdominal pain, nausea, and vomiting. Her blood pressure was severely unstable. Blood laboratory tests revealed elevated catecholamine levels, contrast-enhanced CT of her whole abdomen showed a round retroperitoneal mass with soft tissue density, and somatostatin receptor imaging (68Ga PET-CT) indicated a retroperitoneal mass with abnormally increased expression of somatostatin receptor. It is interesting to note that whole exome sequencing (WES) analyses on both blood and tumor samples revealed a novel EPAS1 mutation, specifically the c.2501A > G; p.Tyr834Cys variant, which has never been reported. The patient was diagnosed with paraganglioma and underwent successful Da Vinci robot-assisted laparoscopic resection of the retroperitoneal tumor. During a 3-month follow-up period, her blood pressure stabilized, and her symptoms significantly improved. Conclusion This case reveals that the EPSA1 mutation may be the primary driver of paraganglioma complicated by atrial septal defect and polycythemia. Additionally, the utilization of Da Vinci robot-assisted laparoscopic surgery contributed to a favorable prognosis for the patient.